1999
DOI: 10.1037/0022-0663.91.1.29
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of phonological processing skills in children learning to read in a second language.

Abstract: English-speaking children (N = 122) in French immersion classes participated in a 1-year longitudinal study of the relation between phonological awareness and reading achievement in both languages. Participants were administered measures of word decoding and of phonological awareness in French and in English as well as measures of cognitive ability, speeded naming, and pseudoword repetition in English only. The relation of phonological awareness in French to reading achievement in each of the languages were eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
228
4
17

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(282 citation statements)
references
References 37 publications
33
228
4
17
Order By: Relevance
“…Their findings indicated that speech perception and phonological awareness are important predictors for reading in English among both students groups. Similar findings were revealed regarding phonological awareness transfer in language pairs German-English (Mann & Wimmer, 2002), Dutch-English (Timmer & Schiller, 2012;Morfidi et al, 2007), Farsi-English (Arab-Moghaddam & Sénéchal, 2001;Gholamain & Geva, 1999), Finnish-English (Dufva & Voeten, 1999), French-English (Comeau, Cormier, Grandmaison, & Lacroix, 1999;Chiang & Rvachew, 2007), Italian-English (D'angiulli et al, 2001), Portuguese-English (da Fontoura & Siegel, 1995), and Russian-English (Abu-Rabia, 2001;Abu-Rabia & Sanitsky, 2010). The findings of all of these studies support Cummins's IH (1979, 1981.…”
Section: Phonological Awarenesssupporting
confidence: 66%
“…Their findings indicated that speech perception and phonological awareness are important predictors for reading in English among both students groups. Similar findings were revealed regarding phonological awareness transfer in language pairs German-English (Mann & Wimmer, 2002), Dutch-English (Timmer & Schiller, 2012;Morfidi et al, 2007), Farsi-English (Arab-Moghaddam & Sénéchal, 2001;Gholamain & Geva, 1999), Finnish-English (Dufva & Voeten, 1999), French-English (Comeau, Cormier, Grandmaison, & Lacroix, 1999;Chiang & Rvachew, 2007), Italian-English (D'angiulli et al, 2001), Portuguese-English (da Fontoura & Siegel, 1995), and Russian-English (Abu-Rabia, 2001;Abu-Rabia & Sanitsky, 2010). The findings of all of these studies support Cummins's IH (1979, 1981.…”
Section: Phonological Awarenesssupporting
confidence: 66%
“…For example, studies Asian-Pacific Journal of Second and Foreign Language Education have revealed that bilingual children's linguistic skills, such as phonological awareness and morphological awareness in their home language, predict their acquisition of English literacy (e.g., Adams, 1990;Casalis & Louis-Alexandre, 2000;Durgunoğlu, 2002;Riches & Genesee, 2006;Snow et al, 1998;Wagner & Torgesen, 1987). In addition, a number of studies examining learning English as an L2 among children who speak an alphabetic L1 like Spanish, French or Italian have found that students' L1 proficiency level can facilitate their L2 learning (e.g., Cisero & Royer, 1995;Comeau et al, 1999;Durgunoglu et al, 1993;D' Angiulli et al, 2001). Despite the evidence of positive crosslinguistic transfer between alphabetic languages, there are fewer studies investigating cross-linguistic transfer between non-alphabetic and alphabetic languages, such as Chinese and English.…”
Section: Introductionmentioning
confidence: 99%
“…Or il reste à mieux préciser, par de nouvelles recherches, jusqu'à quel point, dans le domaine des capacités métalinguistiques, un transfert peut s'opérer entre les différentes langues maternelles et le français langue seconde. Les études menées par Comeau et al (1999) et Cormier et Kelson (2000 auprès d'une population d'élèves anglophones du primaire scolarisés dans des classes d'immersion française montrent l'existence de tels effets de transfert entre les langues en pré-sence, tout au moins en contexte de bilinguisme additif (voir Cummins, 2000). Il serait pertinent d'observer, auprès d'élèves immigrants allophones sous-scolarisés, issus de différentes communautés linguistiques et susceptibles de vivre une situation de bilinguisme soustractif, comment se réalise le développement des capacités métalinguistiques en L1 et en L2, en relation avec l'apprentissage à l'oral et à l'écrit de la langue seconde.…”
Section: Resultsunclassified
“…En langue seconde, un courant de recherche en émergence tend aussi à montrer l'existence d'un lien, en L2, entre les capacités métaphonologiques et la reconnaissance des mots, mais non, ou de façon modérée, entre ces mêmes habiletés et la compréhension de textes, tout au moins avec des apprenants en début d'apprentissage de la langue seconde (Armand, 2000 ;Chiappe et Siegel, 1999 ;Comeau, Cormier, Grandmaison et Lacroix, 1999 ;Lefrançois et Armand, 2003). Les études tendent aussi à montrer l'existence d'une relation entre les capacités en L1 et en L2 et la possibilité d'un transfert en début d'apprentissage de la L1 vers la L2 (Comeau et al, 1999 ;Cormier et Kelson, 2000 ;Durgunoglu, Nagy et HancinBhatt, 1993).…”
Section: Capacités Métalinguistiques Et Langue Secondeunclassified
See 1 more Smart Citation